Intensive Voice Treatment following Botulinum Neurotoxin Injection for a Speaker with Abductor Laryngeal Dystonia: An Exploratory Case Study - Schnell, Mindy; Slavin, Dianne (Seminars in Speech and Language, 2024)
Abductor laryngeal dystonia (ABLD) is a rare neurological voice disorder which results in sporadic opening of the vocal folds during speech. Etiology is unknown, and to date there is no identified effective behavioral treatment for it. It is hypothesized that LSVT LOUD®, which was developed to treat dysphonia secondary to Parkinson's disease, may have application to speakers with ABLD to improve outcomes beyond that with botulinum neurotoxin (BoNT) treatment alone. The participant received one injection of BoNT in each vocal fold 2 to 3 months prior to initiating intensive voice therapy via teletherapy. Objective measures of vocal loudness (dB sound pressure level), maximum phonation time, and high/low pitch frequency (Hz) were recorded in all treatment sessions and follow-up sessions. Over the course of treatment, the participant showed steady gains in phonation time, volume, pitch range, and vocal quality with a substantial reduction in aphonic voice breaks by the end of the treatment program. Perceptual symptoms of ABLD were nearly undetectable by the participant and the clinicians up to 12 months posttreatment, with no additional BoNT injections. The results suggest that LSVT LOUD® following BoNT was effective, with long-lasting improvement in vocal function, for this speaker with ABLD.
Keywords: dysphonia; voice; LSVT; laryngeal dystonia; BoNT